Effect of Vitamin C on In Vitro Maturation of Iraqi She-Camel Oocytes - Karrar Al-Malikey; Dhia Al-Delemi (مجلة الانبار للعلوم البيطرية)
This study aimed to know the effect of vitamin C on in vitro oocytes maturation of Iraqi she-camel with different techniques collection. Several oocytes collection technique have been used: Three hundred ninety oocytes were collected from 84 ovaries from Afak slaughterhouse within half to one hour of slaughter animal and transport by cool box contain normal saline 0.9% (20-25C°) to laboratory of Al-Diwaniyah veterinary Hospital within 1-2 hours. After washing the ovaries with normal saline, each 28 ovaries: oocytes collected by one of the following techniques: Aspiration, slicing, and dissection. Oocytes collected from the three techniques counted and graded. Only grades A and B were selected, and undergo in maturation process. and matured in maturation medium (M199-A) and incubated in CO2 incubator at 5% CO2, 38.5 Cº, and 90% humidity for 24h and supplement the media with 0, 25, 50, 100 µg/ml of vit.C for each technique. Aspirated oocytes were cultured the results was expended cumulus cells was 66.66% (66/99) and the appearance first polar body (F.P.B.) was 68.1% (45/66). Maturation medium supplement with 50µg/ml of vit. C higher rate (84% & 81.8 expended cumulus and F.P.B.) than other groups with significant (P<5%). Maturation oocytes by slicing technique were cultured, expended cumulus was 61.4% (59/96) and the appearance F.P.B. 62.7% (37/59). Maturation medium supplement with 50µg/ml of vit. C (79.16 & 73.68% expended cumulus and F.P.B.) higher rate than other groups with significant (P<5%). Maturation oocytes by dissection technique were cultured. expended cumulus was 57.2% (59/103) and the appearance F.P.B. 55.93% (33/59). Maturation medium supplement with 50µg/ml of vit. C higher rate than other groups with significant (P<5%).